REVITALISASI USAHA KESEHATAN GIGI SEKOLAH (UKGS) DALAM MENINGKATKAN KESEHATAN GIGI DAN MULUT ANAK USIA SEKOLAH - I Gusti Ayu Pradnyani (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2014)
School Dental Care in one of the community health centre (Puskesmas) programs which is intended for families and communities in its vacanity, Such program can be done in house or outdoors of the